Transport network planning - O'Sullivan, Patrick Michael; Holtzclaw, Gary D.; Barber, Gerald M. (London : Croom Helm, 1979)
The control or promotion of the expansion of transport facilities is perhaps the most powerful geographically-specific instrument that government can use to guide economic development.
Includes index.
Includes bibliographical references: p. 174-183.
II 16/01/2019
Loans
Keywords: Transportation - planning